2015
DOI: 10.1016/j.jfda.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oligosaccharides and monosaccharides in Hakka rice wine by precolumn derivation high-performance liquid chromatography

Abstract: This article presents a precolumn derivatization procedure with 1-phenyl-3-methyl-5-pyrazolone (PMP) reagent to detect oligosaccharides and monosaccharides in Hakka rice wine. The subsequent separation of the derivatized glucose-PMP also was performed using a mobile phase consisting of the molar ratio of acetonitrile to ammonium acetate buffer (0.1M) of 22:78 at a flow rate of 1.0 mL/min with the column temperature of 35°C, and the pH of ammonium acetate buffer at 5.5. The optimum derivation conditions were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…PHGG was hydrolyzed using 2 mol/L trifluoroacetic acid (TFA) at 110°C for 4 hr. The sample derivatization and further HPLC analysis procedures applied in this study were determined according to method reported by Bai et al (). The derived samples were analyzed with an Agilent 1200 Infinity HPLC system equipped with an Agilent Eclipse XDB‐C18 column (5 µm, 250 mm × 4.6 mm i.d.).…”
Section: Methodsmentioning
confidence: 99%
“…PHGG was hydrolyzed using 2 mol/L trifluoroacetic acid (TFA) at 110°C for 4 hr. The sample derivatization and further HPLC analysis procedures applied in this study were determined according to method reported by Bai et al (). The derived samples were analyzed with an Agilent 1200 Infinity HPLC system equipped with an Agilent Eclipse XDB‐C18 column (5 µm, 250 mm × 4.6 mm i.d.).…”
Section: Methodsmentioning
confidence: 99%
“…Supernatant aliquots (20 μL) were hydrolyzed by incubation with 0.5 mg/ml amyloglucosidase (10 μL) and 0.1M sodium acetate (10 μL) for 2 hr prior to heating to 100ºC (5 min), followed by cooling to room temperature. Supernatant glycogen concentrations were determined by reverse-phase HPLC in a Hitachi LaChrom Elite® System (Hitachi America, Ltd., Tarrytown, NY), by modification of published methods [Honda et al, 1989;Fuller et al, 2012;Bai et al, 2015]. Hydrolyzed and non-hydrolyzed sample aliquots were derivatized with 100 μL 0.5 M 1-phenyl-3-methyl-5-pyrazolone (PMP) reagent supplemented with 0.3 M NaOH.…”
Section: Glycogen Hplc Analysesmentioning
confidence: 99%
“…Total and resistant starch was measured in several matrices including (e.g., silages) [318]. Bai and coworkers analyzed mono-and oligosaccharides from Hakka rice [319] as a measure of quality for sugars such as isomaltotriose, isomaltose, panose, maltose, and glucose. Finally, the determination of bacterial exopolysaccharides has also been reported [320,331].…”
Section: Complex Carbohydrates and Conjugatesmentioning
confidence: 99%